On the Verge of Civil War: The Need for Scholarship on Police in an Era of Rising Extremism - Blazak, Randy (Criminology, criminal justice, law & society, 2021)
Historians will likely spend countless pages comparing 2020 to 1968. Both years saw large scale urban protests, some violent, as America wrestled with its journey to both maintain and dismantle its own internalized racist culture. Importantly, 1968 was also the year the Johnson Administration released the report of the Kerner Commission. The report, The Challenge of Crime in a Free Society (President’s Commission, 1968), found that the catalysts for the "race riots" that took place in 159 cities during the "long, hot summer" of 1967 were primarily police brutality and racism. Both years were also marked by a presidential election in which the rhetoric of "law and order" was utilized to rally the support of racially fearful white voters, as suburban white voters were urged to support crackdowns on America’s "urban jungles." . . .